Accidental diagnosis of bradyarrhythmia in patients monitored for atrial fibrillation. (19th May 2022) - Diederichsen, SZ; Xing, LY; Frodi, DM; Kongebro, EK; Haugan, KJ; Graff, C; Hoejberg, S; Krieger, D; Brandes, A; Koeber, L; Svendsen, JH
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The study was supported by The Innovation Fund Denmark [12-135225], The Research Foundation for the Capital Region of Denmark [no grant number], The Danish Heart Foundation [11-04-R83-A3363-22625], Aalborg University Talent Management Programme [no grant number], Arvid Nilssons Fond [no grant number], Skibsreder Per Henriksen, R. og Hustrus Fond [no grant number], Medtronic [no grant number], and the AFFECT-EU consortium which has received funding from the European Union's Horizon 2020 research and innovation program under grant agreement No 847770. Background: The interest in heart rhythm monitoring and technologies to detect arrhythmia is increasing. The prevalence and prognostic significance of subclinical bradyarrhythmias is unknown. Objectives: To assess the accidental diagnosis of bradyarrhythmia and its subsequent treatment and prognostic impact in persons screened for atrial fibrillation compared to unscreened persons. Methods: We utilized a randomized trial of ≥70-year-olds with cardiovascular risk factors recruited outside the hospital setting to receive implantable loop recorder screening for atrial fibrillation (ILR group) vs. usual care (Control group). Time-to-event analyses were performed for bradyarrhythmia, pacemaker implantation, syncope, and sudden cardiovascular death. Results: A total of 6004 participants were randomized (mean age 75 years, 47% women, 91% with hypertension, 20% with prior syncope), 4503 to Control and 1501 to ILR. The median follow-up period was 64.5 [59.3, 69.8] months. A total of 675 deaths occurred with an overall rate of 2.16 (2.00-2.33) per 100 person-years, and 67 sudden cardiovascular deaths occurred with a rate of 0.21 (0.15-0.28) for the Control group and 0.23 (0.14-0.37) for the ILR group (hazard ratio (HR) 1.11 (0.64-1.90), p=0.71)). The overall rate of incident bradyarrhythmia was 1.63 (1.49-1.79) per 100 person-years, and bradyarrhythmia was diagnosed in 172 (3.82%) and 312 (20.8%) participants in the Control and ILR group, respectively (HR 6.21 (5.15-7.48), p<0.0001) (Figure 1). The most common bradyarrhythmia was sinus node dysfunction (SND) which was diagnosed in 68 participants in the Control group (1.51%) and 214 in the ILR group (14.26%). In the Control group, 57.35% of diagnoses of sinus node dysfunction resulted in pacemaker implantation, compared to 12.15% in the ILR group where the majority was treated conservatively (Figure 2). The second-most common type of bradyarrhythmia was high-grade atrioventricular block (AVB) which was diagnosed in 86 participants in the Control group (1.91%) and 54 in the ILR group (3.60%). In both groups, the majority of high-grade AVB was treated with pacemaker, although 29.63% in the ILR group were treated conservatively. Risk factors for bradyarrhythmia included higher age, male sex, and prior syncope. Overall, a pacemaker was implanted in 132 (2.93%) and 66 (4.40%) participants (HR 1.53 (1.14-2.06), p<0.0001), syncope occurred in 120 (2.66%) and 33 (2.20%) participants (HR 0.83 (0.56-1.22), p=0.34), and sudden cardiovascular death occurred in 49 (1.09%) and 18 (1.20%) participants (HR 1.11 (0.64-1.90), p=0.71) in the Control and ILR group, respectively. Conclusions: Bradyarrhythmias are highly common in ≥70-year-olds with cardiovascular risk factors. Compared to Control, ILR monitoring led to a six-fold increase in diagnosis of bradyarrhythmia and a significant increase in pacemaker implantations, but no change in the risk of syncope or sudden death.